Nie tylko "sztuka dla sztuki". Poezja patriotyczna na łamach krakowskiego "Życia" (1897-1900) = Not only "art for art`s sake". The patriotic poetry on the pages of Cracovian "Życie" (1897-1900) - Jazownik, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the Polish literature at the turn of the 20th century two concepts of art were clashing - the conceptof the "committed" art and of the autonomous one. An important role in the disputes regarding thecharacter of art had Cracovian "Życie" ("Life"), one of the most important literary magazines of theYoung Poland period.
Keywords: czasopisma literackie; czasopisma polskie; czasopiśmiennictwo polskie - 19 w.